Differences of sex development and surgical decisions: focus group interviews with health care professionals in Norway - Line Merete Mediå; Lena Fauske; Solrun Sigurdardottir; Kristin J. Billaud Feragen; Anne Waehre (Health Psychology and Behavioral Medicine)
Background: Differences of Sex Development (DSD) are congenital conditions where the chromosomal, gonadal and anatomical sex characteristics do not strictly belong to male or female categories, or that belong to both at the same time. Surgical interventions for individuals with DSD remain controversial, among affected individuals, caregivers, and health-care providers. A lack of evidence in support of, for deferring, or for avoiding surgery complicates the decision-making process. This study explores Norwegian health-care professionals’ (HCPs) perspectives on decision-making in DSD-related surgeries and the dilemmas they are facing in this process.Methods: Focus group interviews with 14 HCPs integrated into or collaborating with multidisciplinary DSD teams were analyzed using reflexive thematic analysis.Results: Two overarching dilemmas shed light on the intricate considerations and challenges that HCPs encounter when guiding affected individuals and caregivers through surgical decision-making processes in the context of DSD. The first theme describes how shared decision-making was found to be influenced by fear of stigma and balancing the interplay between concepts of normality, personal experiences and external expectations when navigating the child’s and caregivers’ needs. The second theme illuminated dilemmas due to a lack of evidence-based practice. The core concepts within each theme were the dilemmas health-care professionals face during consultations with caregivers and affected individuals.Conclusion: HCPs were aware of the controversies with DSD-related surgeries. However, they struggled to reconcile knowledge with parents’ wishes for surgery and faced dilemmas making decisions in the best interests of the child. This study draws attention to the benefits of increased knowledge on the consequences of performing or withholding surgery as well as incorporating tools enabling shared decision-making between HCPs and affected individuals/caregivers.